Pinostilbene Hydrate Inhibits the Migration and Invasion of Human Nasopharyngeal Carcinoma Cells by Downregulating MMP-2 Expression and Suppressing Epithelial–Mesenchymal Transition Through the Mitogen-Activated Protein Kinase Signaling Pathways - Tseng, Pao-Yu; Liu, Yen-Tze; Lin, Chia-Chieh; Chuang, Yi-Ching; Lo, Yu-Sheng; Hsi, Yi-Ting; Hsieh, Ming-Ju; Chen, Mu-Kuan (Frontiers in Oncology, 2019)
Background: Nasopharyngeal carcinoma (NPC) is one of the most common head and neck cancers in East and Southeast Asia. During the past decades, advances in radiotherapy and chemotherapy had shown the improvement in tumor control with fewer side effects. Nevertheless, metastasis of NPC causes treatment failure and is often associated with poor clinical outcome and cancer mortality. Hypothesis/Purpose: Pinostilbene hydrate (PSH) was recently demonstrated to have anti-metastatic properties on human oral cancers. However, the effects of PSH on NPC cells remain unknown. Methods and Results: This study aims to investigate the anti-cancer ability of PSH on human NPC by wound healing, transwell assays, zymography assay and Western blot assay to explore the possible underlying mechanisms. PSH significantly reduced the migrated distance of NPC cells in a dose-dependent manner and the abilities of cancer cell migration and invasion were markedly inhibited. The activity and the expression of MMP-2 were also significantly decreased after treatment with PSH. Furthermore, combined treatment of PSH with ERK1/2 inhibitor (U0126) caused significant elevation of the activity and the expression of MMP-2. Additionally, PSH upregulated the expression levels of E-cadherin and Claudin-1 while downregulating that of N-cadherin and vimentin on both NPC cell lines. Conclusion: Our research illustrates that PSH inhibits the migration and invasion of human NPC cells. After exposure to PSH on NPC, the expression of MMP-2 is downregulated and EMT is suppressed through MAPK signaling pathways. These observations suggest that PSH could be a potential anti-metastatic agent for patients with NPC.